2006
DOI: 10.1029/2005gl025433
|View full text |Cite
|
Sign up to set email alerts
|

How do winter thundercloud systems generate sprite‐inducing lightning in the Hokuriku area of Japan?

Abstract: [1] Lightning and thundercloud systems leading to the generation of sprites were examined on the basis of analyses on the interrelation among radar reflectivity, lightning, and static electric field during the winter of 2004/2005 in the Hokuriku area of Japan. Eleven cases from the observed fifteen sprite events exhibit similar characteristics, so we present a typical case study of the thundercloud system. The analysis results are summarized as follows: (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 17 publications
1
46
0
Order By: Relevance
“…Nowadays, sprites are observed in north and south America, Australia, Europe, Taiwan, and Japan ( Barrington-Leigh et al, 2001;Hardman et al, 2000;Neubert et al, 2001;Su et al, 2002;Fukunishi et al, 1999;Hayakawa et al, 2004b;Nakamura and Hayakawa, 2004;Matsudo et al, 2004;Suzuki et al, 2006). However, the significance of observations in different geographical places has not been previously addressed.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Nowadays, sprites are observed in north and south America, Australia, Europe, Taiwan, and Japan ( Barrington-Leigh et al, 2001;Hardman et al, 2000;Neubert et al, 2001;Su et al, 2002;Fukunishi et al, 1999;Hayakawa et al, 2004b;Nakamura and Hayakawa, 2004;Matsudo et al, 2004;Suzuki et al, 2006). However, the significance of observations in different geographical places has not been previously addressed.…”
Section: Introductionmentioning
confidence: 92%
“…Hobara et al, 2006). They mainly occur with positive cloud to ground (CG) lightning, however there are not a negligible number of sprites with negative CG lightning (Barrington-Leigh et al, 1999;Suzuki et al, 2006). Since their optical discovery in 1989 by Franz et al (1990), many papers have appeared on their occurrence, their morphological features, their association with causative lightning, and their associated phenomena (see the reviews, for example, by Rodger, 1999;Williams, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…From the top, we indicated the temporal evolution of number of detected sprite events, the numbers of + and -CGs and the monthly average peak current [kA] for both polarities for each month. The observation is based on the VHF SAFIR system (Suzuki et al, 2006). It follows from this figure that there does not exist any remarkable differences in the properties of lightning discharges during the main three months of sprites (January, February and March), even though there are a few types of weather systems producing lightning in the Hokuriku area as mentioned before.…”
Section: Discussionmentioning
confidence: 72%
“…It is not well understood whether the parent lightning originates from the upper (tilted) positive charge center or from the lower stratiform region (Williams and Yair, 2006). But, Hayakawa et al (2004) and Suzuki et al (2006) have found in the climatic approach that the reservoir of positive charge resides within the stratiform region. Even during the winter, it may be possible that there might exist some fundamental differences in characteristics of lightning discharges, so that this information is plotted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Sprites reported by Lyons [2] and the present study occurred over summer thunderstorms. However, observations of sprites were also reported during winter thunderstorms in Japan and in the eastern Mediterranean [20,21] . Tropical thunderstorms did also produce sprites [22] .…”
Section: Atmospheric Sciencesmentioning
confidence: 85%